Detection of White Spot Syndrome Virus (WSSV) of Shrimp (Litopenaeus vannamei) in UPT Pengembangan Budidaya Air Payau Bangil , Pasuruan District , East Java - Rima Oktavia Kusuma; Muh. Sulaiman Dadiono; Baruna Kusuma; joni Johanda Putra (Universitas Tidar, 2020)
Vanname shrimp (Litopenaeus vanname) is still a favourite in shrimp culture production in Indonesia, since it has faster growth advantages. However, the White spot syndrome virus (WSSV) attack is still a big threat for farmers, because it can proliferates rapidly and cause mass mortality of 90-100%. The UPT Pengembangan Budidaya Air Payau in Bangil maintains vanname and controls virus infection by detecting through a molecular approach. Detection using the Nested PCR method with IQ 2000 kit with molecular weight marker 848 bp, 550 bp, 296 bp. The sample will be tested positive if the bands that appear are in the size 296 bp and / or 550 bp . The results of the detection in shrimp rearing ponds were negative (-) because only the band 848 bp that showed, it was mean the shrimp free from WSSV infection. Water quality data shows that the shrimp rearing environment is in optimal conditions.